Beberapa Senyawa Stilbenoid Dari Kulit Batang Shorea Leprosula Miq. - I Nyoman Adi Winata; Yana Maolana Syah; Sjamsul Arifin Achmad; Euis Holisotan Hakim; Lia Dewi Juliawaty; Emilia L Ghisalberti; M I Choudhary (Institut Teknologi Bandung, 2003)
Three stilbenoid compounds, hopeaphenol (1), laevifonol (2), dan (+)-Î±-viniferin (3) had been isolated from acetone extract of the stem bark of Shorea leprosula Miq. The molecular structures of (1), (2), and (3) was determined based on spectroscopic data, including UV, IR, 1H NMR, and 13C NMR, and comparison with that reported in the literature.